The Impact of Tax Holiday, Tax Allowance, and Effective Tax Rate on Green Investment in Indonesian Geothermal Companies - Arel Agrossia Heresy; Srikalimah; Muhammad Alfa Niam (LP2M IAIN Palopo, 2026)
The development of green investment is a key aspect in supporting a sustainable energy transition in Indonesia, particularly in the geothermal sector. This research analyzes the effects of tax holiday, tax allowance, and effective tax rate on green investment using a quantitative approach, drawing on secondary data from annual reports, sustainability reports, financial statements, official company websites, and publications from IDX. The analysis was conducted using panel data regression with a random effects model. Results reveal tax holiday and tax allowance have advantageous outcome on green investment, whereas the effective tax rate adverse impact. These results implies fiscal incentives can drive an increase in green investment, while a high tax burden has the potential to reduce a company’s capacity to develop sustainable investment activities. This study suggests that tax policy can be utilized as an instrument to strengthen the development of green investment in Indonesia’s geothermal sector.